Pengaruh Harga Dan Kualitas Produk Besi, H Beam x 6m Terhadap kepuasan Pelanggan Pada PT. Sorong Mandiri Sejahtera - Ahcmad, Nardin; Muskita, Susana Magdalena Welly (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2024)
This study aims to analyze the influence of the price and quality of H Beam x6 meter iron products on customer satisfaction who return to buy the product. This research was conducted using a quantitative method using a questionnaire distributed to 56 customers who had returned to buy H Beam x6 meter iron products. The data obtained were analyzed using multiple linear regression. The results of the study showed that there was a significant influence between the price and quality of H beam x6 meter iron products on the satisfaction of customers who returned to buy the product. The influence of price is negative, meaning that the higher the price of the product, the lower the customer satisfaction. The influence of quality is positive, meaning that the higher the quality of the product, the higher the customer satisfaction. This research gives the implication that companies need to pay attention to the price and quality of H beam x6 meter iron products in order to increase customer satisfaction and encourage them to buy the product again. Companies can lower product prices, improve product quality, or offer customer loyalty programs to increase customer satisfaction.